Predictive modelling for cell culture processes in biotherapeutic manufacturing - Panjwani, Shyam (Henry Stewart Talks, 2024)
The need for optimizing cell culture processes in biotherapeutic manufacturing, Key features of a new predictive model to support cell culture processes, Development and validation of the model, Key challenges and how they were met, Wider implications of the model in biopharmaceutical manufacturing